Mathematical Models of Multi-criteria Optimization of Subsystems of Higher Educational Institutions - M.V. Kitaeva; N.V. Speshilova; V. N. Shepel (International Review of Management and Marketing, 2016)
In new conditions an institution for successful work needs optimization of control, adaption of existing mathematical tools and development of new aspects. In the article it is suggested viewing the activities of higher educational institutions as production activities and higher educational institutions as complex organizational and economic systems consisting of a large number of subsystems. The relevance of the research is stipulated on the one hand by insufficient level of implementation of mathematical tools in the management process of both separate elements in the structure of sub-systems and sub-systems themselves, as well as institutions of higher education in general. On the other hand it is stipulated by the necessity to search for new forms and methods of organization and management of the educational process in the context of new educational standards. The conclusion about the interconnection and interdependence of the selected subsystems is made. The directions of further development within the frame of the designated problem are given.